Chiral Conjugated Microporous Polymers as Novel Chiral Fluorescence Sensors for Amino Alcohols. Issue 19 (2nd August 2013) - Wei, Juan; Zhang, Xiaoming; Zhao, Yaopeng; Li, Ruixiang
<x xml:space="preserve">Abstract</x> Novel (R)‐(+)‐1, 1′‐bi‐2‐naphthol ((R)‐(+)‐BINOL)‐based conjugated microporous polymers (CMP1–4) with high Brunauer–Emmett–Teller (BET) surface area are synthesized through Sonogashira–Hagihara cross‐coupling of di‐/tetra‐bromo‐substituted (R)‐(+)‐BINOL derivatives and 1, 3, 5‐triethynylbenzene. Fluorescence studies find that CMP4 can act as a sensitive and enantioselective sensor for chiral amino alcohols, such as 2‐amino‐1‐propanol (AA1), 2‐amino‐3‐methyl‐1‐butanol (AA2), and 2‐amino‐2‐phenylethanol (AA3), which expands the application scope of conjugated microporous polymers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>